A highly sensitive fluorescence assay for methyltransferase activity by exonuclease-aided signal amplification1. Issue 13 (7th July 2015) - Tang, Feng; Xing, Xi-Wen; Chu, Jie-Mei; Yuan, Quan; Zhou, Xiang; Feng, Yu-Qi; Yuan, Bi-Feng
<x xml:space="preserve">Abstract</x> A highly sensitive fluorescence assay for DNA adenine methyltransferase activity was developed using exonuclease-aided signal amplification.